Quali-quantitative Diagnosis of Solid Waste Generated at Campus V of the State University of Pará (Research, Society and Development, 2021)
The generation of solid waste is directly related to human activities, its adequate management is fundamental for the preservation of the environment. For the preparation of plans and projects related to the management of solid waste, it is necessary, primarily, to carry out a quali-quantitative diagnosis of waste in the place where the plan will be implemented. Thus, the present work aimed to carry out a qualitative and quantitative diagnosis of the waste generated at Campus V - Center for Natural Sciences and Technology (CCNT) of the University of the State of Pará and to propose strategies for the better management of this waste. The quali-quantitative analysis took place during the period of one academic week, the quantitative diagnosis was made through the method of quartering described in NBR 10007: 2004 and the classification of residues is carried out according to NBR 10.004: 2004. The results demonstrate that UEPA Campus V produces, on average, 86.26 kg of solid waste weekly, with a per capita generation of 0.098 kg / inhab / day. The residue that presented the highest concentration in the samples carried out was organic (40%), followed by paper / cardboard (35.6%) and plastic (16.9%). Among the alternatives for managing waste are the preparation and implementation of a Solid Waste Plan (PGRS), the promotion of environmental education, the implementation of composting at the university and the establishment of partnerships with cooperatives and recycling associations.